Biofilm Formation and Bio Corrosion of Carbon Steel in Diesel-Biodiesel Storage Tank - Aida Nur Ramadhani; Ardiyan Harimawan; Hary Devianto (Universitas Diponegoro, 2021)
Biodiesel is potential to blend with petroleum diesel as an alternative blended fuel. Biodiesel is usually stored in carbon steel storage tank which easily corroded by microorganisms. Microorganisms can use blended fuels as carbon source and water from biodiesel which is hygroscopic for growth and metabolism. Thus, degradation of fuel may occur and lead to biocorrosion by microorganisms such as Bacillus megaterium. This research was conducted to determine the effect of biodiesel concentration of blended fuel on biofilm formation and biocorrosion by Bacillus megaterium. The experiments were carried out by immersing carbon steel specimens in immersion medium for 21 days with variation of biodiesel concentration (B0, B20, B30, and B100). Biofilms that form on the metal surface cause areas with non-uniform oxygen concentrations and form anodic/cathodic conditions, raised to potential differences and biocorrosion occurred. The average corrosion rates were 0,035 ± 0,03; 0,533 ± 0,33; 0,642 ± 0,28; 0,109 ± 0,04 mm/year achieved by B0, B20, B30 and B100 respectively. These rates increased when compared to the control medium. Microorganism activity also caused damage to the metal surface by forming pitting corrosion on B30 and B100.